2022
DOI: 10.3390/ijerph19010574
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genomic and Bioinformatics Approaches to Identify Molecular Links between Endocrine Disruptors and Adverse Outcomes

Abstract: Exposure to Endocrine Disrupting Chemicals (EDC) has been linked with several adverse outcomes. In this review, we examine EDCs that are pervasive in the environment and are of concern in the context of human, animal, and environmental health. We explore the consequences of EDC exposure on aquatic life, terrestrial animals, and humans. We focus on the exploitation of genomics technologies and in particular whole transcriptome sequencing. Genome-wide analyses using RNAseq provides snap shots of cellular, tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 188 publications
(254 reference statements)
0
4
0
Order By: Relevance
“…Koike et al showed that in mice exposed to DES, constant expression of the lactoferrin and EGF genes can be observed in the vagina and uterus [ 63 ]. Furthermore, Wang et al hypothesized that EGF could stimulate endometriosis cell proliferation by activating the Ras/Raf/MEK/ERK pathway [ 72 , 73 , 74 ].…”
Section: Environmental Impactmentioning
confidence: 99%
“…Koike et al showed that in mice exposed to DES, constant expression of the lactoferrin and EGF genes can be observed in the vagina and uterus [ 63 ]. Furthermore, Wang et al hypothesized that EGF could stimulate endometriosis cell proliferation by activating the Ras/Raf/MEK/ERK pathway [ 72 , 73 , 74 ].…”
Section: Environmental Impactmentioning
confidence: 99%
“…The complex methods by which EEDs affect the genes involved in vascular remodeling and contribute to the onset of PAD are uncovered in this study using gene network analysis. This method makes it easier to identify important genes, their regulatory connections, and probable pathways that EEDs may disrupt, providing insights into the molecular causes of vascular disorders [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting gene network analysis is built on this integrated dataset, which offers a thorough understanding of the molecular dynamics relating to EEDs and vascular remodeling in PAD. Combining bioinformatics methods with various data sources enables a more comprehensive comprehension of the intricate biological mechanisms behind vascular disorders and environmental influences [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of genomic technology, bioinformatics has grown in popularity for analyzing gene expression patterns in order to better understand the molecular processes behind illnesses and to identify meaningful therapeutic targets ( Cantelli et al, 2022 ; Verga et al, 2022 ). Weighted Gene Co-expression Network Analysis (WGCNA) is a critical technique for deciphering gene function and association from genome-wide expression ( Liang et al, 2022 ; Rezaei et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%